2003
DOI: 10.1089/088922203762688612
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intrathecal Release of Soluble Fractalkine in HIV-Infected Patients

Abstract: The CX(3)C chemokine fractalkine is suggested to play an important role in inflammatory brain diseases, for example, because of its chemotactic properties. To investigate the release of soluble fractalkine in HIV-induced brain diseases fractalkine levels were determined in cerebrospinal fluid (CSF) and serum samples of HIV-infected patients with (n = 10) and without (n = 23) HIV-induced CNS complications, using semiquantitative Western blot analysis. Fractalkine CSF levels were significantly elevated (p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Mohamed et al dementia-related literature (31)(32)(33)(34). CD4+ T-cell depletion was related to increased HIV RNA levels in the blood ( R S = 2 0.51, P , .00001), but correlation was lacking with respect to viral levels in the CSF ( R S = 0.29, P , .03; Bonferroni correction: P , .0009).…”
Section: Neuroradiology: Mr Spectroscopic Imaging Factor Analysis In mentioning
confidence: 99%
“…Mohamed et al dementia-related literature (31)(32)(33)(34). CD4+ T-cell depletion was related to increased HIV RNA levels in the blood ( R S = 2 0.51, P , .00001), but correlation was lacking with respect to viral levels in the CSF ( R S = 0.29, P , .03; Bonferroni correction: P , .0009).…”
Section: Neuroradiology: Mr Spectroscopic Imaging Factor Analysis In mentioning
confidence: 99%
“…98 Two studies have demonstrated nonspecific elevations in CSF fractalkine in HIV-positive patients with neurological sequelae including dementia. 99,100 This is not immediately reconciled with in vitro data suggesting fractalkine is neuroprotective. Elevated levels may suggest a host attempt at neuroprotection.…”
Section: Fractalkinementioning
confidence: 94%
“…Several studies showed elevated levels of CX3CL1 in the CSF of patients with HAD compared to controls (healthy individuals, AIDS patients without HAD) and a function of CX3CL1 in HAD was accordingly suggested [123][124][125]. Since an increase of CX3CL1 in CSF was not only found in HAD patients but also under other neurodegenerative conditions, this chemokine might be a general marker for neurodegeneration [126,127].…”
Section: The Role Of Cx3cl1 In Hadmentioning
confidence: 99%
“…Since CX3CL1 is expressed in neurons and released from these cells under stress conditions [131,132] and since microglia express the corresponding chemokine receptor CX3CR1, a role of CX3CL1 in neuron-microglia signaling has been suggested [123][124][125][130][131][132][133]. Indeed, in various models of neurodegeneration and/or neuroinflammation an increase in (neurotoxic)-microglia activity was found when CX3CL1-CX3CR1 signaling was absent [130].…”
Section: The Role Of Cx3cl1 In Hadmentioning
confidence: 99%